TRENDS IN THE PRODUCTION OF KNOWLEDGE ABOUT AUDIOVISUAL EDUCATIONAL TECHNOLOGIES FOR PREGNANT WOMEN - Almeida, Denise Comin Silva; Sehnem, Graciela Dutra; Schmith, Maria Denise; de Mello, Giovana Batistella (Seven Editora, 2025)
Despite the improvements in the health sector in recent decades, studies still show important numbers of maternal deaths related to avoidable causes related to pregnancy, childbirth and puerperium. The objective of this study is to identify the trend of theses and dissertations available in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel on audiovisual educational technologies for pregnant women in prenatal care. This is a documentary, descriptive and exploratory study, using as a search strategy the combination of the terms "educational technology" AND gestation OR audiovisual OR video. After applying the inclusion and exclusion criteria, the research corpus was composed of seven studies, three theses and four dissertations. The studies show concern with emerging themes related to humanized childbirth and prevention of obstetric violence. The development of educational technologies involves important validation and evaluation processes. Two studies brought educational technologies aimed at health promotion in the face of hypertensive syndromes and for the context of oral health of pregnant women. In general, the population has been increasingly looking for quick information, with little reading and many visual resources, with emphasis on the reproduction of short videos that are on the rise on social networks today. It was considered that there is still a gap in the evaluation of educational technologies with a target audience in order to provide reliability and improve the use of the technology or product with specific audiences or from different contexts according to its proposition. DOI: https://doi.org/10.56238/sevened2024.037-165